Quantifying physical and structural soil properties using X-ray microtomography - Tseng, Chien Ling; Alves, Marlene Cristina [UNESP]; Crestana, Silvio (Elsevier, 2018)
One of the current challenges in the study of recovering soil architecture is physically evaluating the internal soil structure in unconventional ways. The elaboration of consistent methods and physical parameters has become necessary for soil structural analysis. The aim of this study is to analyze the soil structures of two groups of recovering tropical soils and to simulate three-dimensional water movement pathways using unconventional methods and physical soil parameters. The following results were obtained from the analysis: 1) the S index was used as an indicator to effectively quantify the degree of management; 2) Qualisolo software was used to obtain the soil water retention curve (SWRC) of each management type; 3) the degree of anisotropy of the solid structure reflected the soil network; 4) the Euler-Poincaré number reflected the connectivity of the soil pores for each management type; 5) the Shannon entropy indicated the degree of randomness of the soil; and 6) the results of the Arya and Paris model and the simulations of water movement pathways are similar. In conclusion, the obtained results reflect the internal soil structures and their corresponding characteristics. Thus, the results can be used to predict the influence of soil architecture on the movement of water in the soil.
Keywords: 3D simulation; Degree of anisotropy; Euler-Poincaré number; Microtomography; S index; Shannon entropy